2018
DOI: 10.1136/jclinpath-2018-205473
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofin vitrosusceptibility of Gram-positive pathogens from a tertiary care hospital in Singapore to a novel oxazolidinone, tedizolid, by a gradient diffusion method and broth microdilution

Abstract: We compared the in vitro antimicrobial activities of tedizolid and linezolid on the Sensititre broth microdilution system for Gram-positive cocci isolates (n=146) from skin and skin structure infections and bloodstream infections, bronchoalveolar lavage and sputum. These pathogens included 40 methicillin-resistant Staphylococcus aureus, 38 coagulase-negative staphylococci, 20 Enterococcus faecalis and 48 beta-haemolytic Streptococcus spp. Susceptibility was simultaneously determined for 48 vanA vancomycin-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Moreover, TDZ shows efficacy against VAN-resistant, daptomycin (DAP)-resistant, and some LNZresistant isolates and hence provides an alternative option to treat the less susceptible isolates of these antimicrobials [35,37,[43][44][45]. Other studies with further Gram-positive isolates mentioned earlier have almost similar findings [11,34,35,38,40,43,[46][47][48][49][50][51][52][53]. However, few isolates that were LNZ resistant (plasmid borne cfr multidrug resistance gene) showed a lower susceptibility (MIC > 0.5 mg/L) [54][55][56][57][58][59].…”
Section: Antimicrobial Spectrummentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, TDZ shows efficacy against VAN-resistant, daptomycin (DAP)-resistant, and some LNZresistant isolates and hence provides an alternative option to treat the less susceptible isolates of these antimicrobials [35,37,[43][44][45]. Other studies with further Gram-positive isolates mentioned earlier have almost similar findings [11,34,35,38,40,43,[46][47][48][49][50][51][52][53]. However, few isolates that were LNZ resistant (plasmid borne cfr multidrug resistance gene) showed a lower susceptibility (MIC > 0.5 mg/L) [54][55][56][57][58][59].…”
Section: Antimicrobial Spectrummentioning
confidence: 61%
“…The non-susceptible isolates displayed an abundant plasmid-mediated ABC transporter optrA [ 50 , 121 ]. Choudhury et al also reported two clinical isolates (out of 48) of vanA E. faecium strains as ‘non-susceptible’ to TDZ (MIC 1–2 mg/L) [ 126 ]. In a recent study, two isolates of E. faecalis displayed TDZ MIC values of 2 mg/L (23S rRNA G2576T mutation).…”
Section: Resistance To Tdz and Pk/pd Targets/magnitudes For Resistant...mentioning
confidence: 99%